If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + -4) + -4x = 2x + -3 + -1(5 + -6x) Reorder the terms: 7(-4 + x) + -4x = 2x + -3 + -1(5 + -6x) (-4 * 7 + x * 7) + -4x = 2x + -3 + -1(5 + -6x) (-28 + 7x) + -4x = 2x + -3 + -1(5 + -6x) Combine like terms: 7x + -4x = 3x -28 + 3x = 2x + -3 + -1(5 + -6x) -28 + 3x = 2x + -3 + (5 * -1 + -6x * -1) -28 + 3x = 2x + -3 + (-5 + 6x) Reorder the terms: -28 + 3x = -3 + -5 + 2x + 6x Combine like terms: -3 + -5 = -8 -28 + 3x = -8 + 2x + 6x Combine like terms: 2x + 6x = 8x -28 + 3x = -8 + 8x Solving -28 + 3x = -8 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -28 + 3x + -8x = -8 + 8x + -8x Combine like terms: 3x + -8x = -5x -28 + -5x = -8 + 8x + -8x Combine like terms: 8x + -8x = 0 -28 + -5x = -8 + 0 -28 + -5x = -8 Add '28' to each side of the equation. -28 + 28 + -5x = -8 + 28 Combine like terms: -28 + 28 = 0 0 + -5x = -8 + 28 -5x = -8 + 28 Combine like terms: -8 + 28 = 20 -5x = 20 Divide each side by '-5'. x = -4 Simplifying x = -4
| 1234x+2=4x-99 | | 4(x-5)=(5-x)4 | | (2v)-4=8 | | 2c-16=10c | | 24x+2=4x+-8 | | b^2=8b-22 | | 9x+2=4x+0.1 | | 2.3-5y=-37 | | X(n+3)=3n+9 | | -log(x)=7.5 | | X(n+3)=3n+8 | | 45x-16=-20x+116 | | 1x+2=4x+3 | | x^3+x^2+9x-19=0 | | 36X+36Y+6K= | | 9x-15=3x-13 | | 7-(-x+1)=9x+6 | | -4x=8x-3 | | 17+x-15=-9 | | 9x-15=5x-13 | | -6+3y=12 | | -13=2x-4x+3 | | 5(1-4)=3(1+2) | | 5x-80=2x-11 | | y=-12x+24 | | 50x+2y=50 | | 0.16b=-12 | | -16=3x-5x-2 | | 3(2m)=x | | 20x-18=54-16x | | 3x+8y+9x+y=90 | | 8=5g-2 |